ANALYSIS OF EVALUATION TECHNIQUES IN THE BOOK "ISLAMIC RELIGIOUS EDUCATION AND ETHICS" FOR ELEVENTH GRADE STUDENTS OF MADRASAH ALIYAH - Rohim, Abd; Al Madzaly, Muhammad Yusri (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The importance of comprehensive evaluation techniques in Islamic Religious Education (PAI) is critical for fostering students' cognitive, affective, and psychomotor development. Purpose: This study analyzes the evaluation techniques in the "Islamic Religious Education and Ethics" textbook for Grade XI students, published by the Ministry of Religion of Indonesia. It examines both test-based and non-test-based approaches, highlighting their limitations in assessing affective and psychomotor aspects critical for student character and skills development. Method: Using qualitative methods, including document analysis and expert interviews, the study suggests incorporating digital-based evaluations to enhance character assessment and religious skills. Result: Recommendations include project-based assessments, interactive multimedia tests, digital portfolios, and game-based learning. Conclusion: The integration of digital tools is proposed to offer a comprehensive evaluation of cognitive, affective, and psychomotor dimensions in religious education.